Male Roles and Responsibilities in Islamic Teachings: A Textual and Literature-Based Analysis - Harli, Harli; Jumadia, Jumadia; AM, Rusydi; Wahyuni, Sri (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
This study examines the roles and responsibilities of men in Islamic society, with particular emphasis on their functions as husbands, fathers, and social leaders. The study aims to explore how Islamic teachings construct men’s moral, social, and spiritual responsibilities and the implications of these constructions for family life and social order. Employing a qualitative approach, this research adopts a literature review and textual analysis of the Quran, Hadith, and relevant academic sources. Data were collected through document analysis and examined using descriptive and interpretative methods to identify key dimensions of male leadership, parenting, family responsibility, and moral education within contemporary contexts. The findings indicate that Islamic teachings position men in multidimensional roles. As husbands, men are responsible for economic provision, protection, and emotional and spiritual support within the family. As fathers, they play a significant role in parenting and in shaping children’s moral values. In the social sphere, men are conceptualized as key actors in leadership, the promotion of justice, and the reinforcement of social cohesion. These findings highlight the importance of a comprehensive understanding of men’s roles in Islam for the development of family education and the discourse on social leadership in contemporary Muslim societies.